Reclaiming Subaltern Voices through Critical Pedagogy: Insights from South African Classrooms - Kudakwashe Mamutse (IQRO: Journal of Islamic Education, 2026)
This paper examines the concept of subalterns and subalternism in education, focusing on the systemic exclusion of marginalised groups from equitable educational opportunities and decision-making processes. Grounded in postcolonial theory, subalternism refers to the marginalisation of socially, politically, and economically oppressed people who lack a voice in dominant societal structures. In education, subaltern groups—such as ethnic minorities, indigenous communities, women, and the economically disadvantaged—face significant barriers to access, representation, and culturally relevant curricula. These barriers perpetuate cycles of inequality, limiting social mobility and reinforcing power imbalances. The paper argues that addressing subalternism in education requires comprehensive critical pedagogical approach that informs comprehensive reforms in curriculum, pedagogy and policy. Curricula should incorporate diverse perspectives and histories that reflect the experiences of marginalised groups, moving beyond dominant, often Eurocentric, narratives. Pedagogical strategies must prioritise inclusivity, equity, and critical thinking, fostering awareness of social justice and empowering students from subaltern backgrounds. Teacher education is also  essential, with an emphasis on cultural competence to ensure educators can effectively engage with diverse student populations. At the policy level, removing systemic barriers such as economic inequality, language exclusion, and geographical isolation is  imperative. Equitable resource distribution, localised curricula, and community participation in educational governance  are identified as key strategies in disrupting entrenched hierarchies. This paper contributes to the discourse on educational equity by proposing a transformative framework that integrates postcolonial and critical pedagogical perspectives to empower subaltern voices and promote social justice in education,